Alveolar Inflammation in Cystic Fibrosis - Ulrich, Martina (2010)
BACKGROUND: In infected lungs of the cystic fibrosis (CF) patients, opportunistic pathogens and mutated cystic fibrosis transmembrane conductance regulator protein (CFTR) contribute to chronic airway inflammation that is characterized by neutrophil/macrophage infiltration, cytokine release and ceramide accumulation. We sought to investigate CF lung inflammation in the alveoli. METHODS: Lung tissue from 14 CF patients and four healthy individuals was analyzed for numbers of effector cells, elastin and collagen concentrations, inflammatory markers and density of Pseudomonas aeruginosa. Additionally, desmosine and isodesmosine concentrations were determined in 52 urine specimens from CF patients to estimate the burden of elastase activities in respiratory secretions. RESULTS: Elastin concentration was significantly decreased and collagen significantly increased in CF alveolar tissues as compared to age-matched, healthy individuals. Elastin split products were significantly increased in urine samples from patients with CF and correlated inversely with age, indicating local tissue remodelling due to elastin degradation by unopposed proteolytic enzymes. Alveolar inflammation was also characterized by a significant cell infiltration of neutrophils, macrophages and T cells, extensive nuclear factor-κB and insulin-like growth factor-1 activation in various cell types and increased intercellular adhesion molecule-1 expression, and increased numbers of myofibroblasts. Additionally, ceramide accumulated in type II alveolar epithelial cells, lacking CFTR. P. aeruginosa organisms were rarely present in inflamed alveoli. CONCLUSIONS: Chronic inflammation and remodeling is present in alveolar tissues of the CF lung and needs to be addressed by anti-inflammatory therapies.